Dinamika Pneumatologis dalam Penginjilan : Analisis Peran Roh Kudus dalam Fase Pra, Proses, dan Pasca Penginjilan - Farida Tawuru May; Etni Grace Andi Yusuf (Sekolah Tinggi Teologi Berita Hidup, 2026)
This study aims to analyze the dynamics of the Holy Spirit’s role in evangelism through a biblical pneumatological approach. The method employed is qualitative descriptive with a literature study of biblical texts and relevant theological sources. The findings reveal that the Holy Spirit is the primary agent in evangelism, working comprehensively in three phases: pre-evangelism, the evangelistic process, and post-evangelism. In the pre-evangelism phase, the Holy Spirit prepares human hearts and initiates divine mission. During the evangelistic process, the Spirit guides evangelists, grants boldness, and convicts individuals of sin. In the post-evangelism phase, the Spirit seals believers, performs regeneration, and guides spiritual growth. These findings affirm that the effectiveness of evangelism does not rely on human ability but on the sovereignty of the Holy Spirit’s work. This study contributes to a more holistic pneumatological framework of mission theology.